The mediating role of electronic information system in the relationship between strategic planning and time management in Jordanian commercial banks - Awwad, Mahmoud Saleem Yousef Eial
In the Jordanian commercial banks, time has to be managed because the provision of high quality services in short amount of time will increase the opportunities of bank to retain as well as increase customers, resulting in the increase of banks' income. Effective time management can be enhanced through electronic information systems. Time management was not given much attention by researchers, in banking sector. Meanwhile, the Jordanian banking sector has little concern of time management, which can lead to the decrease of cu tomers, and this will reflect negatively on the banks' comparative advantages. Strategic planning has now become one of the most important elements of management, and it helps towards the development of banks, and time management can be enhanced through strategic planning. Therefore, the study aims to examine the impact of strategic planning on time management of Jordanian commercial banks, through the mediating factor of electronic information system. Data were obtained randomly from 452 employees working in six Jordanian commercial banks. This study used Structural Equation Modelling (SEM) using IBM - SPSS - AMOS 24.0 for data analysi . The validity and reliability of the measurement and the structural models were confirmed. The results show that strategic planning and electronic information system positively affect time management, while strategic planning positively affects electronic information systems. Also, the results show that electronic information system mediates the relationship between strategic planning an time management. The study concluded that the banking sector in Jordan should be supported to determine the degree of strategic planning, and the designing of the strategic plan for continuous improvement and quality. According to the findings of this research, the study come up with recommendation that: Jordanian commercial banks should continue to improve the practice of startegic planning. This a proach would help them to adapt to internal and external environment and faciliate the adoption of modern electronic information system to provide adequate data and information process.